Synthesis of a leopolic acid-inspired tetramic acid with antimicrobial activity against multidrug-resistant bacteria - Mattio, Luce; Musso, Loana; Scaglioni, Leonardo; Pinto, Andrea; Martino, Piera Anna; Dallavalle, Sabrina (Beilstein Journal of Organic Chemistry, 2018)
The increasing emergence of multidrug-resistant pathogens is one of the biggest threats to human health and food security. The discovery of new antibacterials, and in particular the finding of new scaffolds, is an imperative goal to stay ahead of the evolution of antibiotic resistance. Herein we report the synthesis of a 3-decyltetramic acid analogue of the ureido dipeptide natural antibiotic leopolic acid A. The key step in the synthetic strategy is an intramolecular Lacey–Dieckmann cyclization reaction of a linear precursor to obtain the desired 3-alkyl-substituted tetramic acid core. The synthesized analogue is more effective than the parent leopolic acid A against Gram-positive (Staphylococcus pseudintermedius) and Gram-negative (E. coli) bacteria (MIC 8 µg/mL and 64 µg/mL, respectively). Interestingly, the compound shows a significant activity against Staphylococcus pseudintermedius strains expressing a multidrug-resistant phenotype (average MIC 32 µg/mL on 30 strains tested). These results suggest that this molecule can be considered a promising starting point for the development of a novel class of antibacterial agents active also against resistant strains.
Keywords: antimicrobial activity; multidrug-resistant bacteria; natural products; synthesis; tetramic acid